High-power energy harvesting and imperceptible pulse sensing through peapod-inspired hierarchically designed piezoelectric nanofibers. (August 2022) - Kang, Sukhyun; Kim, Sang Hoon; Lee, Han Bit; Mhin, Sungwook; Ryu, Jeong Ho; Kim, Young Won; Jones, Jacob L.; Son, Yong; Lee, Nak Kyu; Lee, Kangpyo; Kim, Yunseok; Jung, Kyung Hwan; et al.
Abstract: High-performance energy harvesting for human-sensing applications has been achieved through recent progress in piezoelectric-based wearable devices. Piezoelectric nanomaterials can be leveraged for flexibility and biocompatibility while also enhancing piezoelectricity. However, such nanomaterials exhibit low piezoelectricity, limits the industrial-scale development of highly efficient piezoelectric devices. Hence, design of novel materials to significantly enhance piezoelectricity is necessitated. Herein, we demonstrate that a peapod-inspired design in which ZnSnO3 anchored on surface-modified carbon nanotubes (CNT) allows significant enhancement of the piezoelectricity produced by poly(vinylidene fluoride-co-trifluoroethylene)-based (P(VDF-TrFE)-based) nanofibers (a piezoelectric material). The piezoelectric properties were exploited for the application of the as-prepared nanofibers (NFs) in flexible NFs in energy-harvesting and pulse-sensing systems, which demonstrated high output power ((97.5 V and 1.16 μA) as well as imperceptible pulse detection even in posterior tibial arteries. This work provides the scientific and engineering framework for delivering ZnSnO3 -surface-modified CNT-P(VDF-TrFE) NFs excellent piezoelectric performance for use in piezoelectric devices. Graphical Abstract: A nanocomposite comprising poly(vinylidene fluoride-co-trifluoroethylene) nanofibers reinforced with zinc stannate nanoparticles hybridized with surface-modified carbon nanotubes was designed as a piezoelectric source. A device consisting of the nanocomposite between two microbead electrodes showed excellent energy-generation and pulse sensing performances. ga1 Highlights: ZnSnO3 nanoparticles were anchored on the surface modified CNT (ZnSnO3 -SMC) by pulsed laser ablation process. ZnSnO3 -SMC were reinforced within P(VDF-TrFE) nanofibers. ZnSnO3 -SMC-P(VDF-TrFE) nanofibers show excellent piezoelectric performance as well as imperceptible pulsed detection.